Effect of brain acidification on depression-related behaviors in diabetes mellitus - Temma, Yusuke; Obi-Nagata, Kisho; Hoshiba, Yoshio; Miyake, Ryuhei; Katayama, Yuta; Hagihara, Hideo; Suzuki, Norimitsu; Miyakawa, Tsuyoshi; Nakayama, Keiichi I.; Hayashi-Takagi, Akiko (Frontiers in Psychiatry, 2023)
Major depressive disorder (depression) is a leading cause of disability. The severity of depression is affected by many factors, one of which being comorbidity with diabetes mellitus (DM). The comorbidity of depression with DM is a major public health concern due to the high incidence of both conditions and their mutually exacerbating pathophysiology. However, the mechanisms by which DM exacerbates depression remain largely unknown, and elucidating these regulatory mechanisms would contribute to a significant unmet clinical need. We generated a comorbid mouse model of depression and DM (comorbid model), which was extensively compared with depression and DM models. Depressive and anhedonic phenotypes were more severe in the comorbid model. We thus concluded that the comorbid model recapitulated exacerbated depression-related behaviors comorbid with DM in clinic. RNA sequencing analysis of prefrontal cortex tissue revealed that the brain pH homeostasis gene set was one of the most affected in the comorbid model. Furthermore, brain pH negatively correlated with anhedonia-related behaviors in the depression and comorbid models. By contrast, these correlations were not detected in DM or control group, neither of which had been exposed to chronic stress. This suggested that the addition of reduced brain pH to stress-exposed conditions had synergistic and aversive effects on anhedonic phenotypes. Because brain pH was strongly correlated with brain lactate level, which correlated with blood glucose levels, these findings highlight the therapeutic importance of glycemic control not only for DM, but also for psychiatric problems in patients with depression comorbid with DM.